The beneficial influence of combining motor imagery and coach`s feedback on soccer pass accuracy in intermediate players - Robin, N.; Toussaint, L; Joblet, E.; Roublot, E.; Coudevylle, G. R. (Journal of Motor Learning and Development, 2020)
This study compared the effects of motor imagery, feedback, and feedback+imagery interventions on soccer pass performance in non-elite players (intermediate, regional level). Participants were randomly divided into Control, Feedback, Imagery, and Feedback+Imagery groups, within a pre- post- intervention design. The intervention lasted 7 weeks, and the task consisted of passing the ball to a target 20-meters away. In each intervention session, the participants performed 3 blocks of four physical trials. The participants of the Feedback and Feedback+Imagery groups received expert feedback, given by the coach, after each block and then, all the participants realized a mental task (countdown or motor imagery). Results showed that the Feedback+Imagery group had the greatest pre- to post-test improvement compared to the other groups, and highlight the beneficial effect of combining verbal feedback and motor imagery to improve soccer passing accuracy. It is suggested to coaches or physical education teachers to adapt their training by incorporating feedback and imagery.